Properties of the Visible Light Phototaxis and UV Avoidance Behaviors in the Larval Zebrafish - Guggiana-Nilo, Drago A.; Engert, Florian (Frontiers in Behavioral Neuroscience, 2016)
For many organisms, color is an essential source of information from visual scenes. The larval zebrafish has the potential to be a model for the study of this topic, given its tetrachromatic retina and high dependence on vision. In this study we took a step towards understanding how the larval zebrafish might use color sensing. To this end, we used a projector-based paradigm to force a choice of a color stimulus at every turn of the larva. The stimuli used spanned most of the larval spectral range, including activation of its Ultraviolet (UV) cone, which has not been described behaviorally before. We found that zebrafish larvae swim towards visible wavelengths (>400 nm) when choosing between them and darkness, as has been reported with white light. However, when presented with UV light and darkness zebrafish show an intensity dependent avoidance behavior. This UV avoidance does not interact cooperatively with phototaxis towards longer wavelengths but can compete against it in an intensity dependent manner. Finally, we show that the avoidance behavior depends on the presence of eyes with functional UV cones. These findings open future avenues for studying the neural circuits that underlie color sensing in the larval zebrafish.